1994
DOI: 10.1105/tpc.6.3.375
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a Suppressor-mutator/Enhancer-like transposable element, Tpn1, from Japanese morning glory bearing variegated flowers.

Abstract: The Japanese morning glory has an extensive history of genetic studies. Many mutants in the colors and shapes of its flowers and leaves have been isolated since the 17th century, and more than 200 genetic loci have been localized for the 10 linkage groups. They include over 20 mutable loci, several with variegated flower phenotypes. In a line of Japanese morning glory bearing variegated flowers called flecked, a transposable element of 6.4 kb, termed Tpn1, was found within one of the anthocyanin biosynthesis g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(36 citation statements)
references
References 23 publications
2
34
0
Order By: Relevance
“…Much genetic evidence supports the hypothesis that flower variegation is caused by transposable elements inserted into structural genes or regulatory elements related to anthocyanin synthesis [26][28]. The different transcript levels detected in this study for structural genes and TFs might be due to insertions of transposable elements.…”
Section: Discussionsupporting
confidence: 80%
“…Much genetic evidence supports the hypothesis that flower variegation is caused by transposable elements inserted into structural genes or regulatory elements related to anthocyanin synthesis [26][28]. The different transcript levels detected in this study for structural genes and TFs might be due to insertions of transposable elements.…”
Section: Discussionsupporting
confidence: 80%
“…The insertion generated a 3 bp (TGG) target site duplication (TSD), similar to the TSD generated by other CACTA-type transposable elements (Inagaki et al , 1994; Zabala and Vodkin, 2008; Xu et al , 2010). It also contained an ORF for antisense orientation (Fig.…”
Section: Resultsmentioning
confidence: 80%
“…Mutants carrying mutable ct alleles showing somatic reversion to the wild type were reported in the 1930s; however, existing ct mutants showed no mutable phenotypes31. The ct locus was mapped on LG5 of the classical linkage map and was located 1.2 cM from the A3 locus for the anthocyanin biosynthesis gene616. It can be presumed that the CONTRACTED ( CT ) gene is a brassinosteroid (BR) biosynthesis gene, because BR application rescued the deficiency of ct and kobito ( kbt ) double mutants32.…”
Section: Resultsmentioning
confidence: 99%
“…Our recent studies have revealed that many of these mutant lines have been the result of mutagenic activity by Tpn1 family transposons4678910. These transposons are class II elements and members of En/Spm or CACTA superfamily that can transpose via a cut-and-paste mechanism.…”
mentioning
confidence: 99%
See 1 more Smart Citation